2009
DOI: 10.1371/journal.pmed.1000029
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Derived Brain Tumor Following Neural Stem Cell Transplantation in an Ataxia Telangiectasia Patient

Abstract: BackgroundNeural stem cells are currently being investigated as potential therapies for neurodegenerative diseases, stroke, and trauma. However, concerns have been raised over the safety of this experimental therapeutic approach, including, for example, whether there is the potential for tumors to develop from transplanted stem cells.Methods and FindingsA boy with ataxia telangiectasia (AT) was treated with intracerebellar and intrathecal injection of human fetal neural stem cells. Four years after the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
549
2
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 826 publications
(559 citation statements)
references
References 34 publications
(48 reference statements)
3
549
2
5
Order By: Relevance
“…Thus, the risk of tumour initiation of transplanted cells would be increased in injured spinal cords. Actually, a positive correlation between traumatic injury and development of malignancy has recently been reported in the CNS 42 . To support this insight, RNA-seq demonstrated that NSPCs are exposed to various types of stress that could lead to DNA damage after transplantation 2 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the risk of tumour initiation of transplanted cells would be increased in injured spinal cords. Actually, a positive correlation between traumatic injury and development of malignancy has recently been reported in the CNS 42 . To support this insight, RNA-seq demonstrated that NSPCs are exposed to various types of stress that could lead to DNA damage after transplantation 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Amariglio et al 42 reported that transplanted NSPCs gave rise to glioneuronal neoplasms in a patient with ataxia telangiectasia. Although this report is controversial 43,44 , this highlights one of the biggest safety hurdles to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of EV secretion by NPCs introduces a completely different dimension to the therapeutic applications of NPCs in regenerative medicine. By replacing transplantation of NPCs with administration of their secreted products (including EVs), many of the limitations and safety concerns associated with the transplantation of viable replicating cells, such as tumors arising from transplanted NPCs, could be mitigated (Amariglio et al, 2009). …”
Section: Signaling Through Extracellular Membrane Vesiclesmentioning
confidence: 99%
“…66 It may be prudent to have some method of eliminating the transplanted cells (or causing their terminal differentiation) after they have served their function.…”
Section: Resultsmentioning
confidence: 99%